On the Influence of Employment-Breaks on Pension Benefits - Bravo, Jorge (2019)
Bravo, J., & Herce, J. A. (2017). On the Influence of Employment-Breaks on Pension Benefits. (pp. 1-30). (Papers Mi Jubilación; No. 19). Instituto BBVA de Pensiones.